Revision of the fern family Marattiaceae in the Seychelles with two new species and a discussion of the African Ptisana fraxinea complex. - Senterre, Bruno; Rouhan, Germinal; Fabre, Isabelle; Morel, Charles; Christenhusz, Maarten J.m. (Phytotaxa, 2014)
The fern flora of the Seychelles archipelago remains relatively poorly known. Current projects involving the development of the Seychelles National Herbarium and study of key biodiversity areas have resulted in extensive new explorations on the granitic islands. Historical literature, newly collected specimens and older collections have been revised for the fern family Marattiaceae as a prelude for a fern checklist, resulting in the rediscovery of Ptisana a century after it was last reported (as Marattia). Two species of Angiopteris are recognised in the Seychelles, one of them new to science. In total, three species are recorded from the granitic Seychelles islands, Mahé and Silhouette, and none from the coral islands, which are too dry to harbour Marattiaceae. These three species are described in detail. The newly described Angiopteris chongsengiana is characterized by the elongated terminal pinnules and progressively reduced distal pairs of pinnules. Based on phylogenetic molecular analyses the Ptisana fraxinea complex is discussed and several new combinations are proposed. The Seychellois Ptisana is most closely related to Ascension Island endemic P. purpurascens and is described as a new species, Ptisana laboudalloniana. It differs from P. fraxinea in its winged secondary rachises and from P. salicifolia in its smaller habit, with the laminae shorter than broad and shorter than the petioles. Preliminary revisions of other fern families indicate that more discoveries are likely to be made in the fern flora of the Seychelles.